2014
DOI: 10.1261/rna.047126.114
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: diversity of form and function

Abstract: It is now clear that there is a diversity of circular RNAs in biological systems. Circular RNAs can be produced by the direct ligation of 5 ′ and 3 ′ ends of linear RNAs, as intermediates in RNA processing reactions, or by "backsplicing," wherein a downstream 5 ′ splice site (splice donor) is joined to an upstream 3 ′ splice site (splice acceptor). Circular RNAs have unique properties including the potential for rolling circle amplification of RNA, the ability to rearrange the order of genomic information, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
838
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,014 publications
(855 citation statements)
references
References 76 publications
12
838
2
3
Order By: Relevance
“…To date, the evidence suggests that circRNAs may regulate transcription and pathways by manipulating microRNAs. 34,35 The resulting microRNA profiles can act as a distinctive cursor in dividing the induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs); the state of pluripotent stem cell subdivision is of great potential in distinguishing cancer cells from differentiated cells in a p53 network status-related manner. 36 Besides, a negative correlation between global circular RNA abundance and proliferation has been confirmed.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…To date, the evidence suggests that circRNAs may regulate transcription and pathways by manipulating microRNAs. 34,35 The resulting microRNA profiles can act as a distinctive cursor in dividing the induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs); the state of pluripotent stem cell subdivision is of great potential in distinguishing cancer cells from differentiated cells in a p53 network status-related manner. 36 Besides, a negative correlation between global circular RNA abundance and proliferation has been confirmed.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…1 There are 5 general categories of RNA circles, including genomic circular RNA (viroids and hepatitis delta virus), circular intron RNA (circular intronic RNAs and excised introns), circular processing intermediate RNA (rRNA precursors and permuted tRNAs), circular housekeeping noncoding RNA (some snoRNAs and RNase P), and circular spliced-exon RNA. 2 Circular RNA, derived from back-spliced exons anchored by a breakpoint with flanking GU/AG sequence, is essentially exonic circular RNA (circRNA). For nearly 40 years, a systematic and comprehensive understanding of these covalently closed non-colinear RNAs has been lacking because traditional RNA analysis could not provide reliable high-throughput detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, circular RNA molecules (circRNAs) lacking 3 0 or 5 0 termini were considered an unusual form of nucleic acids found in few viroids or viruses using a single-stranded RNA molecule as genetic material, participating in maturation of some tRNA genes, or, alternatively, a result of aberrant RNA splicing (for recent reviews, see [1][2][3] ). However, numerous recent genome-wide experimental and computational studies (RNAseq analyses) tailored toward detection of circRNAs have revealed this class of RNA molecules as abundant in eukarya, including humans.…”
Section: Introductionmentioning
confidence: 99%